Analysis of N6-Methyladenosine Modification Patterns and Tumor Immune Microenvironment in Pancreatic Adenocarcinoma - Liu, Yong; Li, Guangbing; Yang, Yang; Lu, Ziwen; Wang, Tao; Wang, Xiaoyu; Liu, Jun (Frontiers in Genetics, 2022)
Background: Pancreatic adenocarcinoma (PAAD) is a rare cancer with a poor prognosis. N6-methyladenosine (m6A) is the most common mRNA modification. However, little is known about the relationship between m6A modification and the tumor immune microenvironment (TIME) in PAAD. Methods: Based on 22 m6A regulators, m6A modification patterns of PAAD samples extracted from public databases were systematically evaluated and correlated with the tumor immune and prognosis characteristics. An integrated model called the “m6Ascore” was constructed, and its prognostic role was evaluated. Results: Three different m6Aclusters and gene clusters were successively identified; these clusters were characterized by differences in prognosis, immune cell infiltration, and pathway signatures. The m6Ascore was constructed to quantify the m6A modifications of individual patients. Subsequent analysis revealed that m6Ascore was an independent prognostic factor of PAAD and could be a potential indicator to predict the response to immunotherapy. Conclusion: This study comprehensively evaluated the features of m6A modification patterns in PAAD. m6A modification patterns play a non-negligible role in the TIME of PAAD. m6Ascore provides a more holistic understanding of m6A modification in PAAD, and will help clinicians predict the prognosis and response to immunotherapy.